2014
DOI: 10.1002/ijc.28807
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: Serum autoantibodies in the early detection of gastric cancer

Abstract: Antibodies against tumor-associated antigens have been found in serum of patients with various types of cancers and may serve as biomarkers for early detection of gastric cancer as well. This systematic review aims to give an overview about known autoantibodies and their diagnostic value in gastric cancer. We conducted a systematic literature search in two databases to identify studies which performed serological testing for autoantibodies in gastric cancer patients and controls. Data on study characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 56 publications
2
60
0
1
Order By: Relevance
“…Many studies on lung, stomach and colon cancers have confirmed that TAAs and TAA autoantibodies can be used as tools for early diagnosis of cancer and indicators of therapeutic efficacy. Combined detection of p53, c-myc, cyclin-B1 and other TAA autoantibodies with conventional tumor markers can significantly improve the diagnostic specificity and sensitivity [5,[21][22][23]. We have previously demonstrated that expression of TAA autoantibody is increased in patients with other cancers.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many studies on lung, stomach and colon cancers have confirmed that TAAs and TAA autoantibodies can be used as tools for early diagnosis of cancer and indicators of therapeutic efficacy. Combined detection of p53, c-myc, cyclin-B1 and other TAA autoantibodies with conventional tumor markers can significantly improve the diagnostic specificity and sensitivity [5,[21][22][23]. We have previously demonstrated that expression of TAA autoantibody is increased in patients with other cancers.…”
Section: Discussionmentioning
confidence: 96%
“…The human FOXP3 gene is located in Xp11. 23 and contains 11 exons and 10 introns, and the full length of cDNA is 1869 bp. The expression level has been shown to be closely related to tumorigenesis and tumor development [5,6].…”
mentioning
confidence: 99%
“…The immune system is composed of complex networks of molecules and cells that act together to orchestrate the beneficial inflammation needed to maintain and repair the body as well as to protect it from neoplastic cells and invading pathogens (1)(2)(3)(4)(5)(6). Abs binding to body molecules-autoantibodieswould appear to mark the self-reactivity needed for tissue healing (7) and for tumor surveillance (8); autoantibodies also mark autoimmune diseases (9). Thus, it would be important to investigate the characteristics of autoantibodies at birth in healthy humans as a starting point for subsequent evolution of the autoreactive repertoire.…”
mentioning
confidence: 99%
“…37 In recent decades, the potential utility of autoantibodies as cancer biomarkers to monitor therapeutic outcomes, or as indicators of cancer prognosis post-therapy, has been explored. [38][39][40] It was reported the increased anti-NPM1 autoantibody level in the sera from prostate cancer patients after surgery treatment. 41 Using 125 serial serum samples drawn after treatment from 19 LC patients in this study, autoantibody level to both ECH1 and HNRNPA2B1 have not shown variation in the follow-up samples post treatment.…”
Section: Discussionmentioning
confidence: 99%